PELAKSANAAN METODE SAS DALAM KEGIATAN BELAJAR MENGAJAR MEMBACA DAN MENULIS PERMULAAN DI KELAS 2 SDN 2 LOLU - Dedi Siswanto (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to describe the implementation of the SAS Method in Teaching and Reading Activities Beginning and Writing in Class 2 SDN 2 Lolu. The role of the teacher as a manager in learning activities in the classroom has long been recognized as one of the important factors in increasing student achievement. Teachers as professionals are required not only to be able to manage classrooms, namely creating and maintaining conditions in line with government efforts to improve quality at all levels of education, the application of classroom management strategies in learning is one alternative that is believed to be used to solve the fundamental problems of problems in the country